Do emotion regulation, attentional control, and attachment style predict response to cognitive behavioral therapy for anxiety disorders? – an investigation in clinical settings. (8th November 2019) - Nielsen, Sara Kerstine Kaya; Hageman, Ida; Petersen, Anders; Daniel, Sarah Ingrid Franksdatter; Lau, Marianne; Winding, Clas; Wolitzky-Taylor, Kate B; Steele, Howard; Vangkilde, Signe
Abstract: Objective : Approximately, 50% of all individuals with anxiety disorders do not benefit from the "gold standard" treatment, namely cognitive behavioral therapy (CBT). Reliable predictors of treatment effect are lacking. The primary aim of this study was to investigate the predictive value of emotion regulation, attentional control, and attachment style for group-based CBT outcomes in routine clinical settings. Method : A total of 76 patients with anxiety disorders received manual-based group CBT at psychiatric outpatient clinics. Emotion regulation, attachment style, and attentional control were assessed with self-report measures and with an experimental computer-based attentional control task at baseline. The severity of anxiety was assessed at intake, post-treatment, and at a 6-month follow-up. Results : Attentional control, emotion regulation, and attachment avoidance did not predict treatment outcomes. Higher attachment anxiety at baseline was significantly related to poorer outcome. Conclusion : In routine clinical settings, high attachment anxiety may predict poorer outcomes for group-based CBT.